Bleomycin electrochemotherapy for the management of locally advanced metastatic melanoma: Two notable clinical cases potentially indicating a greater therapeutic role in the era of targeted and immuno-therapy - Michael Gallagher; Kuen Yeow Chin; Alastair MacKenzie-Ross (JPRAS Open, 2020)
Summary: Bleomycin electrochemotherapy (ECT) has emerged as a treatment modality for locally advanced metastatic melanoma over the past decade. The phenomenon of reversible electroporation enhances cell permeability when a pulsed electrical current is applied to tissues. This facilitates enhanced cytotoxicity of bleomycin with minimal systemic side effects.We present two case analyses of patients with advanced metastatic melanoma of lower limb which did not respond to alternative therapies, including immunotherapy and isolated limb perfusion, but had a positive clinical response to bleomycin ECT. Locoregional control of the tumour was gained along with positive functional outcomes for the patients including increased mobility and reduced malodour.Bleomycin ECT is an exciting new therapeutic modality in the armamentarium of the plastic surgeon. Operating parameters have been developed and refined which facilitate its safe use along with incorporation into international melanoma guidelines. Evidence in the literature supports its use in select cases, however, it is vital that we share our experiences in its use so that its role can be better defined. Particularly in the era of rapidly developing systemic treatments which are decreasing mortality and thereby increasing the number of patients requiring locoregional disease managment.